ThermoLab for STEM: An Interactive 3D Virtual Lab to Strengthen Students’ Computational Thinking in Heat, Temperature, and Expansion - Wintribrata, Bunaya Hanif; Amelia, Rizki Nor; Listiaji, Prasetyo (Universitas Negeri Surabaya, 2025)
Computational Thinking Skills are among the essential competencies students must master to face the challenges of the digital era. Unfortunately, digital learning media that can effectively enhance students' Computational Thinking Skills, especially through the visualization of abstract science concepts, are still limited. Objectives: This study aims to analyze the feasibility, characteristics, and impact of a STEM-based 3D virtual laboratory on students' computational thinking skills in the topic of temperature, heat, and expansion. Methods: The 3D virtual laboratory was developed using Unity and guided by the ADDIE development model. Results: The media feasibility score was very feasible, and the readability score was well understood. The 3D laboratory had excellent characteristics across five key features: accessibility, observability, realistic scenario simulation, realism, and isolation. In general, computational thinking skills improved, where male students (84.38%) outperformed female students (80.67%), in terms of abstraction, pattern recognition, algorithmic thinking, and generalization, while females were more dominant in decomposition. Novelty: The resulting STEM-based 3D virtual laboratory offers an immersive approach to strengthen Computational Thinking Skills and differs from previous studies that generally only focus on interactive simulations .